Asthma and physical activity in multiracial girls from three US sites. (March 2014) - Vangeepuram, Nita; McGovern, Kathleen J.; Teitelbaum, Susan; Galvez, Maida P.; Pinney, Susan M.; Biro, Frank M.; Kushi, Lawrence H.; Wolff, Mary S.
Abstract Objective: Studies comparing physical activity levels in children with and without asthma have had mixed results. Our objective was to investigate the association between asthma diagnosis and physical activity and to examine differences in these associations by race/ethnicity, weight status and caregiver education. Methods: We investigated the association between asthma (defined as report of physician-diagnosed asthma with at least one asthma related symptom) and measures of physical and sedentary activity in a study of 6- to 8-year-old girls in the Breast Cancer and the Environment Research Project. We compared reported activity and pedometer measurements among girls with and without asthma, and examined modification of these associations by race/ethnicity, weight status and caregiver education. Results: Girls (n = 1182) were included with 33.5% White, 4.8% Asian, 30.6% non Hispanic Black and 30.7% Hispanic. Asthma was present in 16.2% of girls. Overall, 38% of girls reported no participation in organized recreational activities and 58% had >2 h/day of television, video game and computer time combined. Girls with asthma whose parents were less educated reported fewer pedometer steps and less non-scheduled activity than girls without asthma with similar caregiver education level. Among girls with asthma, those on a controller medication had higher levels of sedentary activity and more structured physical activity but were less likely to report high intensity physical activity. Conclusions: Among girls whose parents are less educated, girls with asthma may have lower physical activity levels than girls without asthma. Use of a controller medication may be related to physical and sedentary activity.